2021
DOI: 10.2147/jir.s331579
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors Associated with the Occurrence of Autoimmune Diseases in Patients with Alopecia Areata

Abstract: Background Increased rates of autoimmune diseases (ADs) have been reported in association with alopecia areata (AA); however, the risk factors for coexisting ADs in AA patients have been poorly investigated. Objective To evaluate the prevalence and factors associated with AD comorbidities in patients with AA. Methods This case–control study included patients diagnosed with AA between January 2000 and March 2020. Individuals with AA, both with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Accumulating evidence suggests that hair follicles in the occipital area might elicit less androgen-regulated cellular responses than hair follicles in the other scalp areas ( 22 , 23 ). Frontal hair follicles contained a significantly higher level of androgen receptors and 5α-reductase enzymes, known for converting testosterone into a more potent androgen called dihydrotestosterone, compared to occipital hair follicles for both genders ( 24 27 ). Scalp biopsies also demonstrated a greater amount of aromatase, the enzyme accountable for lowering androgen levels by turning into estrogens, within the occipital rather than the frontal hair follicles in both men and women ( 21 , 24 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that hair follicles in the occipital area might elicit less androgen-regulated cellular responses than hair follicles in the other scalp areas ( 22 , 23 ). Frontal hair follicles contained a significantly higher level of androgen receptors and 5α-reductase enzymes, known for converting testosterone into a more potent androgen called dihydrotestosterone, compared to occipital hair follicles for both genders ( 24 27 ). Scalp biopsies also demonstrated a greater amount of aromatase, the enzyme accountable for lowering androgen levels by turning into estrogens, within the occipital rather than the frontal hair follicles in both men and women ( 21 , 24 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trichoscopy is increasingly used as a non-invasive tool for the diagnosis of hair and scalp disorders ( 6 8 ). Despite the presence of cutaneous signs and laboratory findings, trichoscopic abnormalities may represent the specific features of SA and help differentiate it from other causes of alopecia ( 9 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alopecia areata is accepted as a tissue-specific autoimmune disease that occurs with an environmental triggering factor on the basis of genetic predisposition [ 5 7 ]. Relationships have been reported between alopecia areata and autoimmune diseases such as autoimmune thyroid diseases, vitiligo, type 1 diabetes mellitus and celiac disease [ 8 ]. It has also been reported that atopic conditions such as atopic dermatitis, allergic rhinitis, and asthma are common comorbid diseases in alopecia areata [ 9 ].…”
Section: Introductionmentioning
confidence: 99%